Analysis of Factors Allegedly in Affecting the Performance of Expenditure Treasurer at the Health Polytechnic Work Unit - Lisnah (Journal of Business Issues, 2023)
Management of state finances through the APBN cannot be separated from the performance of the treasurer, both the expenditure treasurer and the receiving treasurer. In the budget cycle, especially in the stages of accountability and budget execution, one can find the role of expenditure treasurer who must be able to carry out his authority and duties using good performance. Performance is influenced by many factors, including hard skills, soft skills, and motivation. Therefore, this ability is always related to other people and himself who manage his skills. This study aims to analyze the factors that influence the performance of expenditure treasurers at the Work Unit of the Health Polytechnic. The research method uses a cross-sectional study design. The research began in March 2023 in all Work Units of the Health Polytechnic in the Directorate General of Health Workers (Dirjen Nakes) of the Ministry of Health which is spread throughout Indonesia. The number of samples used was 38 employees who were taken using the total sampling technique. Data collection was measured using a questionnaire via the Google Form link with a Likert scale which was filled in directly by the respondents. Data were analyzed using a hypothesis testing test that began with the F test (ANOVA), t-test, and analysis of the Coefficient of Determination (R2). The test results show that 3 factors influence the performance of the expenditure treasurer at the Health Polytechnic Work Unit, namely hard skills, soft skills, and motivation of 0.771 or 77.1%. So therefore, the Directorate General of Health Workers which oversees all health polytechnics in Indonesia, can improve the ability of employees by providing training that is relevant to the competencies of the APBN PK Functional Position, in this case, the expenditure treasure, hence producing better performance of themselves.